Perkembangan Motivasi Peserta Didik di Sekolah Dasar - Mustofa, Nurul Hadi; Darsinah, Darsinah; Wulandari, Murfiah Dewi (Lembaga Yasin AlSys, 2022)
The development of motivation is one of the tasks of student development. A student is expected to have great motivation in learning activities in order to be able to understand the learning material. Motivation is needed by students in learning activities because motivation can encourage students to do something in order to achieve the goals of learning activities. Without motivation, student learning activities will not take place optimally. The higher the motivation of students, the higher the learning outcomes obtained. The research used is literature review research. The data used is secondary data collected in one unit to answer the formulated problems. Therefore, educators are at the forefront to raise the motivation of their students in participating in learning. Educators must understand the development of student motivation and the problems of student motivation, especially in elementary schools.